Regulating The Use Of Smart Contract In Indonesia - Saputri , Fitri Arianti (Jurnal Hukum dan Keadilan, 2024)
There are many characteristics of the industrial revolution 4.0, one of which is the rapid development of technology, one of which is the existence of smart contracts. A smart contract is an agreement made by two or more parties that is generated automatically from a code guaranteed by a technology called blockchain. Nick Szabo was the first to introduce smart contracts. In Indonesia, smart contracts do not yet have specific arrangements in their implementation. There are only basic arrangements regarding agreements, namely in Book III of the Civil Code to be precise in Article 1320, as well as arrangements regarding electronic contracts in Government Regulation Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions. However, even though this smart contract only contains basic rules, it does not make it an agreement that is prohibited by the government, as long as an agreement or contract does not conflict with the law and meets the basic requirements, an agreement can be legally binding. Therefore, in this writing, it is necessary to further examine what are the rules governing smart contracts in Indonesia. The research method applied in this paper is to use qualitative normative juridical, which is a separate focus in describing a problem related to regulations or rules that exist in Indonesia. The results of this study will then find a broader elaboration of regulations for the use of smart contracts in Indonesia and how this smart contract system can work using blockchain technology.